Effects of Hydrolyzed Yeast on Weanling Pig Growth Performance and Stress-related Blood Antioxidant Criteria - Jessica L. Smallfield; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt; Robin Yao; Yitong Guo (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 360 weanling pigs (241 × 600 DNA; initially 11.9 ± 0.03 lb) were used in a 45-d study to evaluate the effects of hydrolyzed yeast (HY; Ceretide S, Planet Bioscience; Boon Lay Way, Singapore) on growth performance, fecal dry matter, stress-relevant blood antioxidant criteria, and circulating cytokine concentrations. Pens of pigs were randomly allotted to one of six dietary treatments in a generalized randomized block design with five pigs per pen and 12 pens per treatment. Pigs were blocked so there were four replications each of light, medium, and heavyweight pens per treatment. Diets were corn-soybean meal-based and consisted of a negative control diet (NC), a positive control diet (PC), which was the negative control diet + 55 mg/kg carbadox (Mecadox 2.5, Phibro; Teaneck, NJ), the positive control diet with 0.04% HY (Ceretide S, Planet Bioscience; Boon Lay Way, Singapore), and the negative control diet with either 0.04, 0.08, or 0.12% HY. Treatment diets were fed in three phases from d 0 to 10 (phase 1), d 10 to 24 (phase 2), and d 24 to 45 (phase 3). On d 10 and 24, fecal samples were collected from the same three randomly selected pigs in each pen to determine fecal dry matter (DM) and fecal scores. Blood samples were collected on d 10 and 45 from the same representative pig in each pen for total antioxidant capacity (TAC), superoxide dismutase (SOD), and cytokine panel. The interactive effect of HY and carbadox were tested, and no significant responses (P > 0.10) were observed. From d 0 to 10 (phase 1), there was a main effect of carbadox, where pigs fed either diet containing carbadox had increased (P ≤ 0.025) ADG and d 10 BW compared with the mean of those not fed carbadox with either none or 0.04% HY. From d 10 to 24 (phase 2), F/G improved (P = 0.041) when 0.04% HY was added to the PC and NC diets. From d 24 to 45 (phase 3), ADFI increased (P = 0.041) for pigs fed diets containing carbadox compared to pigs not fed carbadox, which led to a tendency for ADG to increase (P = 0.087) with carbadox inclusion. Overall (d 0 to 45), final BW increased (P = 0.026) and ADG tended to increase (P = 0.058) for pigs fed diets containing carbadox compared to pigs fed diets without carbadox. Also, F/G improved (P = 0.017) when 0.04% HY was added to the PC and NC diets. For fecal DM on d 10, increasing HY in diets without carbadox increased fecal DM (linear, P = 0.005). Also, pigs fed carbadox had increased (P ≤ 0.009) fecal DM on d 10 and 24 compared to pigs fed similar diets without carbadox. On d 10, cytokines GM-CSF, IL-2, IL-4, and TNFα decreased then increased (quadratic, P < 0.05) and IL-1α, IL-1β, IL-6, and IL-10 tended to decrease then increase (quadratic, P < 0.10) as the inclusion of HY increased in diets without carbadox, with the lowest concentration observed at an inclusion level of 0.08% HY and 0.04% for GM-CSF. On d 45, TAC decreased (linear, P = 0.008) as the inclusion level of HY increased. In summary, pigs fed carbadox with or without 0.04% HY had increased overall ADG and fecal DM. Adding 0.04% HY with carbadox improved feed efficiency compared to pigs fed carbadox alone. Additionally, feeding 0.04% HY tended to improve F/G with further reduction in serum cytokine concentration levels at an inclusion of 0.08%.
Keywords: cytokine production; hydrolyzed yeast; nursery pig; total antioxidant capacity